2017
DOI: 10.1051/0004-6361/201731759
|View full text |Cite
|
Sign up to set email alerts
|

Colour variations in the GRB 120327A afterglow

Abstract: Aims. We present a comprehensive temporal and spectral analysis of the long Swift GRB 120327A afterglow data to investigate the possible causes of the observed early time colour variations. Methods. We collected data from various instruments/telescopes in different bands (X-rays, ultra-violet, optical and near-infrared) and determined the shapes of the afterglow early-time light curves. We studied the overall temporal behaviour and the spectral energy distributions from early to late times. Results. The ultra-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…A gravitational wave (GW) event originated by the merger of a binary neutron star (BNS) system was detected for the first time by aLIGO/Virgo (GW 170817; Abbott et al 2017a), and it was found to be associated to the weak short GRB 170817A detected by the Fermi and INTEGRAL satellites (Goldstein et al 2017;Savchenko et al 2017), marking the dawn of multi-messenger astronomy (Abbott et al 2017b). The proximity of the event (∼ 41 Mpc; Hjorth et al 2017, Cantiello et al, ApJ in press) and the relative accuracy of the localization (∼ 30 deg 2 , thanks to the joint LIGO and Virgo operation) led to a rapid (∆t < 11 hr) identification of a relatively bright optical electromagnetic counterpart (EM), named AT2017gfo, in the galaxy NGC 4993 (Arcavi et al 2017;Coulter et al 2017;Lipunov et al 2017;Melandri et al 2017;Tanvir et al 2017;Soares-Santos et al 2017;Valenti et al 2017). The analysis and modelling of the spectral characteristics of this source, together with their evolution with time, resulted in a good match with the expectations for a "kilonova" (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A gravitational wave (GW) event originated by the merger of a binary neutron star (BNS) system was detected for the first time by aLIGO/Virgo (GW 170817; Abbott et al 2017a), and it was found to be associated to the weak short GRB 170817A detected by the Fermi and INTEGRAL satellites (Goldstein et al 2017;Savchenko et al 2017), marking the dawn of multi-messenger astronomy (Abbott et al 2017b). The proximity of the event (∼ 41 Mpc; Hjorth et al 2017, Cantiello et al, ApJ in press) and the relative accuracy of the localization (∼ 30 deg 2 , thanks to the joint LIGO and Virgo operation) led to a rapid (∆t < 11 hr) identification of a relatively bright optical electromagnetic counterpart (EM), named AT2017gfo, in the galaxy NGC 4993 (Arcavi et al 2017;Coulter et al 2017;Lipunov et al 2017;Melandri et al 2017;Tanvir et al 2017;Soares-Santos et al 2017;Valenti et al 2017). The analysis and modelling of the spectral characteristics of this source, together with their evolution with time, resulted in a good match with the expectations for a "kilonova" (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…References: GRB 060418 (Dupree et al 2006;Mundell et al 2007a;Schady et al 2007;Molinari et al 2007;Tsvetkova et al 2021), GRB 091208B (Wiersema et al 2009;Nakajima et al 2009;Uehara et al 2012;Schady et al 2012;Nava et al 2012), GRB 100805A (Oates et al 2012;Steele et al 2017), GRB 120327A (Perley & Tanvir 2012;D'Elia et al 2014;Steele et al 2017;Melandri et al 2017;Tsvetkova et al 2021), GRB 131030A (Breeveld & Troja 2013;de Ugarte Postigo et al 2013;Xu et al 2013;King et al 2014;Littlejohns et al 2015;Tsvetkova et al 2017) and GRB 141220A (de Ugarte Postigo et al 2014a;Tsvetkova et al 2017;this work).…”
Section: Discussionunclassified
“…The solid vertical line of GRB 060418 is the peak time of the fireball deceleration. References: GRB 060418 (Mundell et al 2007a;Molinari et al 2007), GRB 091208B (Nakajima et al 2009;Uehara et al 2012), GRB 100805A (Steele et al 2017), GRB 120327A (Steele et al 2017;Melandri et al 2017) and GRB 131030A (Breeveld & Troja 2013;King et al 2014).…”
Section: Polarization From Collisionless Shocksmentioning
confidence: 99%
“…Moreover, Morgan et al (2014) found a significant decrease of visual extinction A V over a time period of t ∼ 10 − 100 s, which is proposed as a first evidence of dust destruction toward GRB 120119A. In particular, late-time observations usually reveal a rebrightening in optical-NIR light curves of GRB afterglows (Greiner et al 2013;Nardini et al 2014;Melandri et al 2017;Kann et al 2018). The origin of such an optical re-brightening remains elusive (see e.g., Nardini el al.…”
Section: Introductionmentioning
confidence: 97%